Aqueous zinc metal battery electrolyte and applications thereof

CN116826200BActive Publication Date: 2026-10-09CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310413648.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-18
Publication Date
2026-10-09
Estimated Expiration
2043-04-18

AI Technical Summary

Technical Problem

但关于含氮杂环化合物作为水系锌金属电池电解液添加剂的相关报道还鲜有记载

Benefits of technology

[0027] When 1,4,7,10-tetraazacyclododecane (cyclen) is used as an additive in the electrolyte of an aqueous zinc metal battery, unlike other small-molecule polymer additives, the four nitrogen atoms in the cyclic alkane additive can coordinate and complex with zinc ions. This alters the solvation structure of zinc ions in the electrolyte, expelling some water molecules coordinated with zinc ions and delivering zinc ions to the zinc metal anode surface more quickly. This significantly inhibits hydrogen evolution corrosion of the zinc metal anode and the formation of insulating hydroxides. Furthermore, the outer cycloalkyl group has a hydrophobic effect, isolating water and protecting zinc ions, further reducing hydrogen evolution corrosion of the zinc metal anode and the formation of hydroxide byproducts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116826200B_ABST
    Figure CN116826200B_ABST
Patent Text Reader

Abstract

The application belongs to the field of electrochemical energy storage and new energy materials, and relates to a water-based zinc metal battery, in particular to a water-based zinc metal battery electrolyte and application thereof. The water-based zinc metal battery electrolyte contains water, zinc ions and an additive; the additive is 1,4,7,10-tetraazacyclododecane, and the concentration of the additive in the electrolyte is 0.02-0.1 mol / L. The application protects the zinc metal negative electrode by adding 1,4,7,10-tetraazacyclododecane into the electrolyte containing zinc ions at a certain molar ratio. The electrolyte additive can be complexed with zinc ions, change the solvation structure of zinc ions and water, inhibit various side reactions of the zinc negative electrode, effectively prevent the growth of dendrites and corrosion on the surface of the zinc negative electrode, and realize long-term cycling of the zinc metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical energy storage and new energy materials, and relates to aqueous zinc metal batteries, specifically to an aqueous zinc ion electrolyte and its application. Background Technology

[0002] With the development of human society, the energy used by people has undergone phased changes. Due to the invention of the internal combustion engine in the early 20th century, oil has been used as an efficient fuel ever since. However, the widespread use of oil has caused many negative impacts. For example, when it is burned, it produces a large amount of carbon dioxide, carbon monoxide, sulfur dioxide and other pollutants that pollute the air and seriously affect people's quality of life. At the same time, oil, coal and other fuels are non-renewable resources and face the crisis of energy shortage. Therefore, people have begun to focus on exploring the use of renewable energy.

[0003] The widespread application of electricity has brought numerous conveniences to people. Hydropower, thermal power, and nuclear energy provide a guarantee for large-scale power supply, while new energy generation methods such as wind and solar power also show great promise, with significant research results in recent years. Currently, batteries are the primary storage medium for electrical energy, and reusable secondary batteries are more environmentally friendly and have a wider range of applications. Among the many types of batteries, lithium-ion batteries have been successfully commercialized and mass-produced due to their advantages such as high energy density, low cycle loss, and long lifespan. However, lithium-ion batteries also have many drawbacks. For example, they use flammable and volatile organic electrolytes, resulting in poor safety performance. Furthermore, the conditions required for manufacturing lithium-ion batteries are quite demanding, requiring an oxygen- and water-free environment. The increasing scarcity of lithium resources also keeps the cost of lithium batteries high. Therefore, solving battery safety issues and reducing costs have become the main challenges.

[0004] Zinc metal batteries offer greater environmental friendliness and safety compared to lithium-ion batteries. They utilize aqueous electrolytes instead of organic electrolytes, addressing safety concerns and improving the electrolyte's ionic conductivity. Furthermore, the use of naturally abundant zinc metal as the anode enhances safety and significantly reduces costs. Additionally, zinc metal batteries exhibit a high volumetric energy density (5851 mA h cm⁻¹). -3 Similar to lithium-ion batteries, zinc metal batteries also utilize Zn. 2+ Storing and releasing electrical energy by inserting / de-inserting into positive and negative electrodes has advantages such as large capacity, fast charging and discharging speed, and high reversibility over long cycles, and has a very broad development prospect.

[0005] However, the rapid development of zinc metal batteries in recent years has also exposed many problems. During charge-discharge cycles, zinc metal batteries preferentially deposit in the form of dendrites due to the tip discharge effect on the zinc metal surface. As the number of battery cycles increases, the dendrites gradually grow, eventually piercing the separator and causing a short circuit. In addition, due to the special solvation structure of zinc ions with water, many side reactions occur on the zinc metal anode, such as hydrogen evolution reaction producing hydrogen gas that causes battery bulging, and zinc oxidation reaction forming insulating zinc hydroxide. Currently, there has been preliminary progress in optimizing the zinc metal anode. The first is direct modification of the zinc anode surface, such as coating the zinc anode with an organic / electrode layer, which plays a role in corrosion inhibition and promoting nucleation, suppressing the growth of zinc dendrites. The second is modification of the zinc metal structure, such as alloying zinc metal, utilizing the larger electrochemically active area of ​​the current collector, allowing Zn to peel off / grow in a planar manner. However, the above two methods are generally accompanied by complex process steps and negative impacts from changing the battery structure. Therefore, the final method of improving the electrolyte with additives is the most realistic.

[0006] Currently, commonly used electrolyte additives are mainly produced in two ways. One is to add transition metal or heavy metal ions, which, with their more negative redox potential, can be adsorbed at the tip of the zinc anode to form a protective layer and inhibit the rampant growth of dendrites. However, when used on a large scale, heavy metal ions can cause environmental pollution and are relatively expensive. The other is to add a small amount of organic additives. Organic additives can adsorb on the surface of the zinc anode, inducing zinc ions to deposit in a plane, and can also change the solvation structure of zinc ions, inhibiting hydrogen evolution corrosion and enabling zinc metal batteries to achieve long-term cycling.

[0007] Search results reveal that nitrogen-containing heterocyclic compounds have been reported as electrolyte additives in lithium-ion battery electrolytes. For example, patent CN201910230659.9 reports the addition of 0.1-10 wt% of electron-withdrawing substituents to nitrogen-containing heterocyclic compounds (e.g., 1,4,7,10-tetrabenzenesulfonyl-1,4,7,10-tetraazacyclododecane) in an organic solvent system. The electron-withdrawing substituents in these compounds result in high oxidation potentials, preventing oxidation of the designed lithium-ion battery during cycling and allowing them to function as complexing agents. Furthermore, these electron-withdrawing substituents exhibit good compatibility with carbonate electrolytes, without affecting the electrolyte's physical properties. The electron-withdrawing substituents can also undergo complexation reactions with high-valence nickel ions, thereby improving complexation efficiency and increasing the stability of the complex. However, reports on nitrogen-containing heterocyclic compounds as additives in aqueous zinc-metal battery electrolytes are still scarce. Summary of the Invention

[0008] Addressing the shortcomings of existing technologies, this invention is the first to utilize 1,4,7,10-tetraazacyclododecane (cyclen) as an additive in an aqueous zinc-metal battery electrolyte. By dissolving the additive in a prepared aqueous zinc-ion electrolyte at a specific molar ratio, the zinc anode of the zinc-metal battery is protected. This additive can adsorb onto the zinc anode surface, inducing zinc ions to deposit via planar diffusion. Simultaneously, it improves the solvation structure of zinc ions, significantly suppressing hydrogen evolution corrosion and various side reactions occurring on the anode surface.

[0009] To achieve the above objectives, the technical solution of the present invention is as follows:

[0010] This invention discloses an aqueous zinc metal battery electrolyte containing water, zinc ions, and an additive; the additive is 1,4,7,10-tetraazacyclododecane (cyclen); the concentration of the additive in the electrolyte is 0.02–0.1 mol / L.

[0011] The general chemical formula of 1,4,7,10-tetraazacyclododecane (cyclen) in this invention is:

[0012]

[0013] Preferably, the concentration of the additive in the aqueous zinc metal battery electrolyte is 0.04–0.08 mol / L and the molar ratio of the additive to zinc ions is 0.025–0.05:1, more preferably 0.028–0.032:1, and even more preferably 0.03:1.

[0014] Preferably, the concentration of zinc ions in the aqueous zinc metal battery electrolyte is 1.5-3 mol / L; more preferably, it is 1.9-2.1 mol / L.

[0015] Preferably, in the aqueous zinc metal battery electrolyte, zinc ions are provided by ZnSO4, Zn(CF3SO3)2, or ZnSO4+Zn(CF3SO3)2. ZnSO4 is preferred.

[0016] Preferably, in the aqueous zinc metal battery electrolyte, zinc ions are provided by ZnSO4, and the concentration of zinc is 1.95-2.05 mol / L; the concentration of the additive 1,4,7,10-tetraazacyclododecane is 0.055-0.065 mol / L.

[0017] The aqueous zinc metal battery electrolyte of the present invention is prepared by: taking water-soluble zinc salt and additives according to the designed grouping, adding the prepared water-soluble zinc salt and additives to water, stirring evenly, and obtaining the aqueous zinc metal battery electrolyte.

[0018] The present invention relates to an application of an aqueous zinc metal battery electrolyte, the application comprising using the aqueous zinc metal battery electrolyte in a zinc metal battery; the aqueous zinc metal battery comprising a positive electrode, a negative electrode, a separator, and a battery electrolyte.

[0019] This invention relates to the application of an aqueous zinc metal battery electrolyte, wherein the negative electrode is zinc metal.

[0020] This invention relates to the application of an aqueous zinc metal battery electrolyte, wherein the battery includes a Zn||Zn symmetric cell and a zinc metal full cell.

[0021] This invention relates to the application of an aqueous zinc metal battery electrolyte, wherein the positive electrode is selected from zinc metal, vanadium-based oxides (V₂O₅, V₂O₅, V₂O₅). x O y M x V y O z Vanadates, V x O y ·nH2O、M x V y O z The anode material is at least one of the following: H2O, manganese-based oxides (α-MnO2, β-MnO2, δ-MnO2, ZnMn2O4, etc.), Prussian blue analogues (PBAs, ZnHCF, CuHCF, CoFe(CN)6, etc.), and organic materials (PANI, PANI / CFs, PANI-GO / CNTs, PANI-CNTs-PEDOT, PANI-CNTs-TPU, CC-PANI-FeCN, PANI / Graphene, PANI / Carbon Fiber, PANI / Cellulose Papers, etc.); the negative electrode is zinc metal.

[0022] The diaphragm is selected from at least one of glass fiber, single-layer PP, single-layer PE, PP+ceramic coating, PE+ceramic coating, double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP, Nafion, PVDF, porous polymer membrane, non-woven diaphragm, and inorganic composite membrane.

[0023] This invention relates to the application of an aqueous zinc metal battery electrolyte, wherein the battery includes all zinc metal batteries, including but not limited to Zn||Zn symmetric cells, Zn||Cu half-cells, Zn||Ti half-cells, Zn||V2O5 full cells, and Zn||MnO2 full cells.

[0024] This invention relates to the application of an aqueous zinc metal battery electrolyte, resulting in a Zn||Zn symmetric battery with a cycle life greater than or equal to 320 hours. After optimization, this can be achieved to greater than or equal to 1500 hours. Further optimization results in a cycle life greater than or equal to 2400 hours.

[0025] The zinc metal full battery designed and prepared in this invention exhibits a cycle capacity retention rate greater than 21.4% under high current conditions. After optimization, the capacity retention rate can reach greater than or equal to 51.0%, and with further optimization, it can reach greater than or equal to 89.8%. After even further optimization, the capacity retention rate can reach greater than or equal to 90.9%. The high current condition refers to a current density greater than or equal to 3 A g. -1 The situation.

[0026] When the obtained Zn||V2O5 full cell uses zinc metal as the negative electrode, glass fiber as the separator, V2O5 as the positive electrode, and an aqueous solution of 2 mol / L Zn(CF3SO3)2 containing 0.06 mol / L 1,4,7,10-tetraazacyclododecane (cyclen) as the electrolyte, its capacity retention rate is greater than or equal to 90% after 2000 cycles.

[0027] When 1,4,7,10-tetraazacyclododecane (cyclen) is used as an additive in the electrolyte of an aqueous zinc metal battery, unlike other small-molecule polymer additives, the four nitrogen atoms in the cyclic alkane additive can coordinate and complex with zinc ions. This alters the solvation structure of zinc ions in the electrolyte, expelling some water molecules coordinated with zinc ions and delivering zinc ions to the zinc metal anode surface more quickly. This significantly inhibits hydrogen evolution corrosion of the zinc metal anode and the formation of insulating hydroxides. Furthermore, the outer cycloalkyl group has a hydrophobic effect, isolating water and protecting zinc ions, further reducing hydrogen evolution corrosion of the zinc metal anode and the formation of hydroxide byproducts. Attached Figure Description

[0028] Figure 1 The chemical structure diagram of 1,4,7,10-tetraazacyclododecane (cyclen);

[0029] Figure 2 The graphs show the cycle life test results of zinc symmetric batteries in Comparative Example 1 and Examples 1-3.

[0030] Figure 3 This is a battery performance graph for Example 4.

[0031] Figure 4 The linear voltammetric scan test results are for Comparative Example 1 and Example 2.

[0032] Figure 5The images show the cycle life test results of zinc symmetric batteries for Comparative Example 2 and Example 4; where a is a scanning electron microscope (SEM) image of the zinc sheet after 100 cycles of the symmetric battery with zinc sulfate as the electrolyte; and b is a scanning electron microscope (SEM) image of the zinc sheet after 100 cycles of the symmetric battery with zinc sulfate and additives as the electrolyte.

[0033] Figure 6 The hydrogen evolution test curves of Zn||Ti half-cell LSVs are shown for Comparative Example 1 and Examples 1, 2, and 3.

[0034] Figure 7 The charge-discharge cycle diagrams are for the Zn||V2O5 full cells of Comparative Example 4 and Examples 8, 9, and 10.

[0035] Figure 8 Rate plots of Zn||V2O5 full cells for Comparative Example 4 and Examples 8, 9, and 10. Detailed Implementation

[0036] This invention uses 1,4,7,10-tetraazacyclododecane (cyclen) as an additive for aqueous zinc metal batteries, and its structural formula is as follows: Figure 1 As shown, it can achieve long-term cycling of zinc metal batteries.

[0037] In this invention, the conditions for testing the cycle life of the battery are as follows:

[0038] The Zn||Zn symmetric cells and Zn||V2O5 full cells prepared in the comparative examples below were subjected to charge-discharge cycle tests using the Newway battery testing system, and the Zn||Ti half cells were subjected to electrochemical performance tests using the IviumStat electrochemical workstation.

[0039] The constant-temperature charge-discharge experimental conditions were as follows: the products of the comparative example and the embodiment were tested as symmetrical batteries at 30°C, and the current density of the Zn||Zn symmetrical battery during charge-discharge was 1 mA cm⁻¹. -2 The charging and discharging times are both 1 hour; the Zn||V2O5 full cell operates at 0.1 A g. -1 After 20 cycles of activation under current, perform 3A g -1 High-current charge-discharge cycle.

[0040] The experimental conditions for hydrogen evolution potential testing were as follows: the assembled Zn||Ti half-cell was tested on an IviumStat electrochemical workstation at 1 mV s. -1 The speed range was tested from 0.1V to -0.5V.

[0041] 1. Preparation of additive-modified aqueous zinc metal battery electrolyte:

[0042] (1) Dissolve 20 mmol of ZnSO4 in 10 ml of deionized water and stir magnetically until a clear solution is obtained to prepare a 2 mol / L ZnSO4 aqueous electrolyte.

[0043] (2) Dissolve 20 mmol of Zn(CF3SO3)2 in 10 ml of deionized water and stir magnetically until a clear solution is obtained to prepare a 2 mol / L Zn(CF3SO3)2 aqueous electrolyte.

[0044] (3) Dissolve 10 mmol of ZnSO4 and 10 mmol of Zn(CF3SO3)2 in 10 ml of deionized water and stir magnetically until a clear solution is obtained to prepare 1 mol / L ZnSO4 + 1 mol / L Zn

[0045] (CF3SO3)2 aqueous electrolyte.

[0046] (4) Add 0.02-0.1 mol of 1,4,7,10-tetraazacyclododecane (cyclen) to the electrolyte prepared above and stir magnetically until completely dissolved to prepare an additive-modified aqueous zinc metal battery electrolyte.

[0047] 2. Assemble an aqueous zinc metal battery:

[0048] A Zn||Zn symmetric cell was assembled using zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and an aqueous solution of 2 mol / L ZnSO4, Zn(CF3SO3)2, and containing 0.02-0.1 mol / L 1,4,7,10-tetraazacyclododecane (cyclen) as the electrolyte.

[0049] Comparative Example 1: A Zn||Zn symmetrical cell was assembled using zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and 2 mol / L ZnSO4 aqueous solution as the electrolyte. The cell was named ZS Zn||Zn.

[0050] Comparative Example 2: Using zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and 2 mol / L Zn(CF3SO3)2 aqueous solution as the electrolyte, a Zn||Zn symmetric cell was assembled and named ZF Zn||Zn.

[0051] Comparative Example 3: Using zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and 1 mol / L ZnSO4 + 1 mol / L Zn(CF3SO3)2 aqueous solution as the electrolyte, a Zn||Zn symmetrical cell was assembled and named 1ZS+1ZF Zn||Zn.

[0052] Comparative Example 4: A Zn||V2O5 full cell was assembled using zinc metal as the negative electrode, glass fiber as the separator, vanadium pentoxide as the positive electrode, and 2 mol / L Zn(CF3SO3)2 aqueous solution as the electrolyte. The cell was named ZF Zn||V2O5.

[0053] Example 1: A Zn||Zn symmetric cell was assembled using zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and an aqueous solution of 2 mol / L ZnSO4 containing 0.02 mol / L 1,4,7,10-tetraazacyclododecane (cyclen) as the electrolyte. The cell was named ZS1CZn||Zn. Its performance is shown in […]. Figure 2 .

[0054] Example 2: A Zn||Zn symmetric cell was assembled using zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and an aqueous solution of 2 mol / L ZnSO4 containing 0.06 mol / L 1,4,7,10-tetraazacyclododecane (cyclen) as the electrolyte. The cell was named ZS3CZn||Zn. Its performance is shown in […]. Figure 2 .

[0055] Example 3: A Zn||Zn symmetric cell was assembled using zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and an aqueous solution of 2 mol / L ZnSO4 containing 0.1 mol / L 1,4,7,10-tetraazacyclododecane (cyclen) as the electrolyte. The cell was named ZS5CZn||Zn. Its performance is shown in […]. Figure 2 .

[0056] Example 4: A Zn||Zn symmetric cell was assembled using zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and a 2 mol / L aqueous solution of Zn(CF3SO3)2 containing 0.06 mol / L 1,4,7,10-tetraazacyclododecane (cyclen) as the electrolyte. The cell was named ZF3CZn||Zn. Its performance is shown in […]. Figure 3 .

[0057] Example 5: A Zn||Zn symmetric cell was assembled using zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and an aqueous solution of 1 mol / L ZnSO4 + 1 mol / L Zn(CF3SO3)2 containing 0.02 mol / L 1,4,7,10-tetraazacyclododecane (cyclen) as the electrolyte. The cell was named 1ZS+1ZF 1C Zn||Zn. Its performance is shown in […]. Figure 4 .

[0058] Example 6: A Zn||Zn symmetric cell was assembled using zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and an aqueous solution of 1 mol / L ZnSO4 + 1 mol / L Zn(CF3SO3)2 containing 0.06 mol / L 1,4,7,10-tetraazacyclododecane (cyclen) as the electrolyte. The cell was named 1ZS+1ZF 3C Zn||Zn. Its performance is shown in […]. Figure 4 .

[0059] Example 7: A Zn||Zn symmetric cell was assembled using zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and an aqueous solution of 1 mol / L ZnSO4 + 1 mol / L Zn(CF3SO3)2 containing 0.1 mol / L 1,4,7,10-tetraazacyclododecane (cyclen) as the electrolyte. The cell was named 1ZS+1ZF 5C Zn||Zn. Its performance is shown in […]. Figure 4 .

[0060] Example 8: A Zn||V2O5 full cell was assembled using zinc metal as the negative electrode, glass fiber as the separator, V2O5 as the positive electrode, and a 2 mol / L aqueous solution of Zn(CF3SO3)2 containing 0.02 mol / L 1,4,7,10-tetraazacyclododecane (cyclen) as the electrolyte. The cell was named ZF1CZn||V2O5. Its battery performance is shown in […]. Figure 7 , 8 .

[0061] Example 9: A Zn||V2O5 full cell was assembled using zinc metal as the negative electrode, glass fiber as the separator, V2O5 as the positive electrode, and a 2 mol / L aqueous solution of Zn(CF3SO3)2 containing 0.06 mol / L 1,4,7,10-tetraazacyclododecane (cyclen) as the electrolyte. The cell was named ZF3CZn||V2O5. Its performance is shown in […]. Figure 7 , 8 .

[0062] Example 10: A Zn||V2O5 full cell was assembled using zinc metal as the negative electrode, glass fiber as the separator, V2O5 as the positive electrode, and a 2 mol / L aqueous solution of Zn(CF3SO3)2 containing 0.1 mol / L 1,4,7,10-tetraazacyclododecane (cyclen) as the electrolyte. The cell was named ZF5CZn||V2O5. Its performance is shown in […]. Figure 7 , 8 .

[0063] A comparative graph of the charge-discharge cycles of the Zn||Zn symmetric batteries in Comparative Example 1 and Examples 1-3 is presented, as follows: Figure 2As shown. The battery cycle life of Comparative Example 1 is about 80 hours, while the cycle life of Example 1 reaches 400 hours, Example 2 reaches 2400 hours, and Example 3 reaches 1700 hours.

[0064] Comparative Example 1 and Example 2 were cycled simultaneously for 100 cycles. The batteries were then disassembled, and the morphology of the zinc negative electrode was observed using a scanning electron microscope. Figure 5 As shown in (a) and (b). A comparison reveals that after 100 cycles in an additive-free electrolyte, as... Figure 5 (a) Zinc deposition on the zinc anode surface exhibits a growth trend perpendicular to the surface. These upright zinc dendrites easily pierce the separator, leading to a short circuit in the battery, which also corresponds to the short cycle life problem of symmetrical batteries. However, after 100 cycles in an electrolyte with additives, as... Figure 5 (b) The zinc deposition on the zinc anode surface is flat and uniform, and the zinc is deposited in a two-dimensional plane, showing an orderly layer-by-layer stack.

[0065] By testing the comparative and example samples using a linear voltammetric method on an electrochemical workstation, the strength of the hydrogen evolution corrosion tendency on the zinc anode surface can be determined. For example... Figure 6 As shown, a more negative potential means that the hydrogen evolution reaction is more difficult to occur. Compared with Comparative Example 1, the potential of Example 1 decreased from -0.102 to -0.115V, the potential of Example 2 decreased to -0.126V, and the potential of Example 3 decreased to -0.131V, indicating that the 1,4,7,10-tetraazacyclododecane (cyclen) additive in the ZnSO4 electrolyte successfully inhibited the hydrogen evolution corrosion reaction.

[0066] A comparative graph of the charge-discharge cycles of the Zn||Zn symmetric battery in Comparative Example 2 and Example 4 is presented, as follows: Figure 3 As shown. The battery cycle life of Comparative Example 2 was around 80 hours, while that of Example 4 reached 820 hours. The same effect was observed in different electrolyte systems, demonstrating the universal applicability of the 1,4,7,10-tetraazacyclododecane (cyclen) additive.

[0067] A comparative graph of the charge-discharge cycles of the Zn||Zn symmetric batteries in Comparative Example 3 and Examples 5-7 is presented, as follows: Figure 4 As shown. The battery cycle life of Comparative Example 3 is about 84 hours, while the cycle life of Example 5 reaches 640 hours, the cycle life of Example 6 reaches 380 hours, and the cycle life of Example 7 reaches 320 hours.

[0068] A comparative graph of the charge-discharge cycles of the Zn||V2O5 full cells in Comparative Example 4 and Examples 8-10 was used, as shown in the figure. Figure 7 As shown. In 3A g -1Under high current conditions, the capacity retention rate of the battery in Comparative Example 4 was only 21.4% after 2000 cycles, while the capacity retention rates of the batteries obtained in Examples 8-10 were 51.0%, 90.9%, and 89.8%, respectively, after 2000 cycles. The addition of additives greatly improved the cycle stability of zinc metal full batteries and extended the service life of the full batteries.

[0069] The rate performance of the Zn||V2O5 full cells in Comparative Example 4 and Examples 8-10 is compared graphically, as follows: Figure 8 As shown, under different current conditions, the batteries of Examples 8-10 all exhibit higher specific capacity compared to Comparative Example 4.

Claims

1. An aqueous zinc metal battery electrolyte, characterized in that: The aqueous zinc metal battery electrolyte contains water, zinc ions, and an additive; the additive is 1,4,7,10-tetraazacyclododecane; the concentration of the additive in the electrolyte is 0.02~0.1 mol / L.

2. The aqueous zinc metal battery electrolyte according to claim 1, characterized in that: The concentration of the additive in the aqueous zinc metal battery electrolyte is 0.04~0.08 mol / L and the molar ratio of the additive to zinc ions is 0.025~0.05:

1.

3. The aqueous zinc metal battery electrolyte according to claim 2, characterized in that: In aqueous zinc metal battery electrolytes, the molar ratio of additives to zinc ions is 0.028~0.032:

1.

4. The aqueous zinc metal battery electrolyte according to claim 1, characterized in that: The concentration of zinc ions in the aqueous zinc metal battery electrolyte is 1.5-3 mol / L.

5. The aqueous zinc metal battery electrolyte according to claim 4, characterized in that: The concentration of zinc ions in the aqueous zinc metal battery electrolyte is 1.9-2.1 mol / L.

6. The aqueous zinc metal battery electrolyte according to claim 1, characterized in that: In aqueous zinc metal battery electrolytes, zinc ions are provided by at least one of ZnSO4, Zn(CF3SO3)2, and ZnCl2.

7. The aqueous zinc metal battery electrolyte according to claim 6, characterized in that: In the aqueous zinc metal battery electrolyte, zinc ions are provided by ZnSO4, and the concentration of zinc is 1.95-2.05 mol / L; the concentration of the additive 1,4,7,10-tetraazacyclododecane is 0.055-0.065 mol / L.

8. The application of an aqueous zinc metal battery electrolyte as described in any one of claims 1-6, characterized in that: The application includes using an aqueous zinc metal battery electrolyte in a zinc metal battery; the aqueous zinc metal battery includes a positive electrode, a negative electrode, a separator, and a battery electrolyte; the negative electrode is zinc.

9. The application of the aqueous zinc metal battery electrolyte according to claim 8, characterized in that: The positive electrode is selected from at least one of zinc metal, vanadium-based oxides, manganese-based oxides, Prussian blue analogues, and organic materials; the negative electrode is zinc metal. The diaphragm is selected from at least one of the following: glass fiber membrane, single-layer PP membrane, single-layer PE membrane, PP+ceramic coated membrane, PE+ceramic coated membrane, double-layer PP / PE membrane, double-layer PP / PP and triple-layer PP / PE / PP membrane, Nafion membrane, PVDF membrane, porous polymer membrane, non-woven diaphragm, and inorganic composite membrane.

Citation Information

Patent Citations

  • A lithium-ion battery electrolyte and a lithium-ion battery

    CN111755746B

  • Nonaqueous electrolyte for secondary battery and nonaqueous electrolyte secondary battery using same

    CN111048841A

  • Electrolyte additive

    CN115911473A